Oral microbiota as promising diagnostic biomarkers for gastrointestinal cancer: a systematic review - Chen, Yanwei; Chen, Xuechen; Yu, Haixin; Zhou, Haibo; Xu, Shu (OncoTargets and therapy, 2019)
Oral Microbiota as Promising Diagnostic Biomarkers for Gastrointestinal Cancer: A Systematic Review